Association between dietary habits and emotional and behavioral problems in children: the mediating role of self-concept - Zhao, Dong; Xiao, Wenhan; Tan, Boren; Zeng, Ye; Li, Shuting; Zhou, Jiali; Shan, Shiyi; Wu, Jing; Yi, Qian; Zhang, Ronghua; Su, Danting; Song, Peige (Frontiers in Nutrition, 2025)
IntroductionIncreasing research has focused on the influence of diet on mental health and well-being. This study aimed to investigate dietary habits status and their associations with emotional and behavioral problems (EBPs) in pre-teen children, as well as explore the mediating effect of child self-concept in the associations between healthy dietary habits and EBPs.MethodsA cross-sectional survey using stratified random sampling was conducted to recruit third-grade children and their caregivers. Dietary habits and self-concept were assessed with self-administrated questionnaires in children. Information on children’s EBPs was collected through questionnaires completed by their caregivers. Multilevel logistic regression models were used to estimate the associations between dietary habits and self-concept and EBPs, respectively. The mediation analysis was employed to test the mediating role of self-concept in the association between dietary habits and EBPs.ResultsOf 1,126 caregiver-child dyads (Mean age of children: 9.53, 52.8% boys) included, only 37.4 and 54.2% of children met the healthy standard of milk/soy milk and fruit, respectively. Healthy fresh fruit (odds ratio [OR] = 0.57, 95% confidence intervals [CI] 0.40–0.78) and vegetables intake (OR = 0.54, 95% CI 0.38–0.76) were associated with a higher self-concept while frequent consumption of sweet foods (OR = 1.58, 95% CI 1.05–2.36) and street foods (OR = 1.61, 95% CI 1.14–2.28) were associated with a lower self-concept. Children who had unhealthy sugar-sweetened beverages intake were at an elevated risk of EBPs (OR = 1.41, 95% CI 1.03–1.95). Moreover, the relationship between healthy dietary habits and EBPs was mediated by self-concept (indirect effect β = −0.09, p < 0.001, total effect β = −0.13, p < 0.001), the proportion of mediation was 29%.ConclusionThis study revealed that the dietary habits of pre-adolescents need improvement, and dietary habits of certain foods, such as fresh fruits and sugar-sweetened beverages, were significantly associated with child mental health. Furthermore, dietary practices were related to the reduced EBPs through an enhanced self-concept. The findings provide an evidence base for developing dietary improvement strategies for pre-adolescent children in families, schools, and other health service settings, thereby contributing to the United Nations’ Sustainable Development Goals related to zero hunger and good health and well-being.